2018
DOI: 10.1002/jcp.26592
|View full text |Cite
|
Sign up to set email alerts
|

Notch activation promotes osteoblast mineralization by inhibition of apoptosis

Abstract: Notch activator Jagged1 (JAG1) plays a critical role in the regulation of osteoblast differentiation and bone metabolism. In this study, JAG1-induced osteoblast proliferation, differentiation, and mineralization has been analyzed in primary osteoblasts for up to 7 days. Alkaline phosphatase and Alizarin red staining showed an enhanced osteoblast maturation and mineralization in JAG1 treated cells, as well as higher mRNA levels of late osteoblast differentiation markers. In contrast, Notch inhibitor DAPT and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…But the possible mechanism was not shown. Recent studies have shown that BMP-Smad, Notch, and Wnt/β-Catenin signaling pathway play important roles in osteogenic differentiation of cells [ [61] , [62] , [63] , [64] , [65] ]. Therefore, in this study we hypothesized that the osteogenic effects of MCNTs were related to these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…But the possible mechanism was not shown. Recent studies have shown that BMP-Smad, Notch, and Wnt/β-Catenin signaling pathway play important roles in osteogenic differentiation of cells [ [61] , [62] , [63] , [64] , [65] ]. Therefore, in this study we hypothesized that the osteogenic effects of MCNTs were related to these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The cell apoptosis was detected by the Annexin V FITC apoptosis detection kit (BD Biosciences, San Jose, CA, United States) as we described previously (Xu et al, 2018). Briefly, on Days 1, 4, and 7 after cell sheet culture, the cells were washed with PBS and trypsinized.…”
Section: Analysis Of Apoptotic Cellsmentioning
confidence: 99%
“…Consistent with this finding, our study further showed that Notch ligand Jagged1-mediated primary osteoblast mineralization was enhanced through decreased cell apoptosis in a caspase 3edependent manner. 24 A similar effect also was observed in cultures of primary human bone marrowederived mesenchymal stem cells (MSCs). When human bone marrowederived MSCs were transduced with lentiviral vectors containing either human NICD1 or ligand jagged1, the cultures showed an enhanced mineralization.…”
Section: Tezuka Et Al 21 Examined the Role Of Notch Activation Inmentioning
confidence: 61%